(untitled) - Marsh, Lisa (Hoboken, N.J., 2003)
Includes bibliographical references (p. 217-219) and index.; Quỹ Châu Á
Keywords: Fashion designers -- Biography -- United States; Fashion design -- History -- 20th century -- United States; Nhà thiết kế thời trang -- Tiểu sử -- Hoa Kỳ (Mỹ); Thiết kế thời trang -- Lịch sử -- Hoa Kỳ (Mỹ) -- Thế kỷ 20